2018
DOI: 10.1037/hea0000515
|View full text |Cite
|
Sign up to set email alerts
|

APOE e4-genotype and lifestyle interaction on cognitive performance: Results of the LIFE-Adult-study.

Abstract: Our findings suggest that the dementia risk variant of the APOE gene does not alter the association between lifestyle factors and cognitive performance in the general population aged 40- to 79-years-old. However, as lifestyle factors impact cognitive aging, research efforts should focus on establishing effective interventions promoting healthy lifestyle behaviors to counteract adverse cognitive aging processes. (PsycINFO Database Record

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 53 publications
0
15
0
Order By: Relevance
“…9,10 There have been instances of null results, however. 11 It is also possible that there is a degree of file-drawer where null results are less likely to be published. 12 There have been few large-scale systematic investigations into whether APOE e4 interacts with lifestyle risk factors associated with worse cognitive abilities in a single cohort with a standard methodologic procedure.…”
mentioning
confidence: 99%
“…9,10 There have been instances of null results, however. 11 It is also possible that there is a degree of file-drawer where null results are less likely to be published. 12 There have been few large-scale systematic investigations into whether APOE e4 interacts with lifestyle risk factors associated with worse cognitive abilities in a single cohort with a standard methodologic procedure.…”
mentioning
confidence: 99%
“…Other studies noted a cognitive gain for APOE e4‐allele carriers through intellectual lifestyle activities. For instance, Rodriguez et al 22 found associations between higher occupational attainment and better cognitive functioning. Wirth et al 23 and Arenaza‐Urquijo et al 24 observed a lower amount of Alzheimer pathology in APOE e4 carriers if they had higher lifetime cognitive activity.…”
Section: Discussionmentioning
confidence: 99%
“…And this method (Single nucleotide polymorphisms (SNPs) at nucleotides 112 and 158 of the gene were amplified by PCR using Taq DNA polymerase and a thermal profile were optimized for the locus. By identifying the alleles present at the 112 and 158 polymorphisms, APOE genotype was defined) had been described by Donohoe et al33 According to the methods previously described,34 these 228 subjects were divided into three groups, e2 (ε2/ε2 and ε2/ε3, n=35), e3 (ε3/ε3, n=152), and e4 (ε2/ε4, ε3/ε4, and ε4/ε4, n=41).35 And Table 2 lists the information about the gene distribution in detail.…”
Section: Methodsmentioning
confidence: 99%